EVALUATION OF THERMAL PROPERTIES AND PERMEABILITY OF BIOPLASTIC FILMS BASED ON STARCH, ALOE VERA AND GRAPHENE. - Puca Pacheco, Mercedes (2022)
The aim of this research was to obtain bioplastic films based on potato starch, graphene and aloe vera to study the effect of varying the content of these components on the thermal and permeability properties of the bioplastic. The water vapor barrier property is being of great interest in the study of bioplastic materials since materials with low permeability to water vapor are needed in the packaging industry to ensure the conservation of packaged products and are an alternative to conventional plastics. According to the results, two thermal decomposition zones were found, the first in the range of 100 to 280°C and the second around 300°C. A minimum value of permeability and permeability of 5,35 kg/h.kPa.m2 and 0,001839 kg/h.kPa.m, respectively, was also found at a graphene concentration of 0,005%w/w; aloe concentration of 24% w/w; and starch concentration of 10% w/w.